2013
DOI: 10.1016/j.pain.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between stimulus intensity and perceptual load in the attentional control of pain

Abstract: The interaction between intensity of nociceptive stimuli and cognitive load in a concomitant task is still a challenging and complex topic. Here, we investigated the interaction between top-down factors (i.e., perceptual load), induced by a visual task, and bottom-up factors (i.e., intensity of nociceptive stimuli that implicitly modifies saliency of input). Using a new experimental paradigm, in which perceptual load is varied while laser heat stimuli of different intensities are processed; we show a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 38 publications
5
48
1
2
Order By: Relevance
“…This is in contrast to previous studies indicating that distraction or directing attention away from a noxious stimulus reduces the intensity of pain (McCaul and Malott 1984;Miltner et al 1989;Romero et al 2013;Van Damme et al 2008;Van Ryckeghem et al 2011). However, in most studies, the distraction from a noxious stimulus either coincided with a cognitive task requiring a large amount of attentional resources (Miltner et al 1989) or switching to another sensory modality (Bauer et al 2006;Garcia-Larrea et al 1997;Romero et al 2013;Van Damme et al 2008). In the present study, subjects retrospectively rated the average pain intensity of laser and electrical stimuli, respectively, after each recording block.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to previous studies indicating that distraction or directing attention away from a noxious stimulus reduces the intensity of pain (McCaul and Malott 1984;Miltner et al 1989;Romero et al 2013;Van Damme et al 2008;Van Ryckeghem et al 2011). However, in most studies, the distraction from a noxious stimulus either coincided with a cognitive task requiring a large amount of attentional resources (Miltner et al 1989) or switching to another sensory modality (Bauer et al 2006;Garcia-Larrea et al 1997;Romero et al 2013;Van Damme et al 2008). In the present study, subjects retrospectively rated the average pain intensity of laser and electrical stimuli, respectively, after each recording block.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with Agostinho et al [33] we propose that persistent pain might lead to a centrally mediated impairment of non-painful thermal percept as shown previously in clinical and experimentally-induced pain [30], [34], [35]. Additionally, ongoing pain might reallocate attentional and/or working memory resources [36], [37] or processing of pain-related material [38], [39] possibly resulting in increases of sensory thresholds [40], [41].…”
Section: Discussionsupporting
confidence: 84%
“…High-frequency gamma activity has long been associated with cognition and attention [8,9] but has also been shown to encode ongoing pain [10,11]. Moreover, surgically implanted devices such as spinal cord stimulation have shown the potential to modulate cortical gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) activity [12], supporting the hypothesis of supraspinal mechanisms of action for spinal, and potentially peripheral, neuromodulation.…”
Section: Introductionmentioning
confidence: 93%
“…Of the patients included in the MEG analysis experiencing pain during the study (n = 11), five reported 50% or greater reduction in reported pain scores with DRGS, while one reported worsening of pain. DRGS-mediated pain relief was associated with a significant reduction in gamma activity (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) Hz) across all MEG sensors during task performance (t = 2.27, p = 0.036) (See Figure 5A). The observed reduction in gamma band activity during pain relief was predominantly localized to the prefrontal cortex based on source-space analyses, but also revealed reductions in gamma activity in both somatosensory and anterior cingulate cortices after 3D source reconstruction (See Figure 5B).…”
Section: Gamma Band Activitymentioning
confidence: 99%